(untitled) (Research, Society and Development, 2025)
The repeatability for fruit characters and the number of measurements needed to evaluate of pataua palm (Oenocarpus bataua Mart.) germplasm were estimated. A sample of five fruits was taken from 31 genotypes conserved at Embrapa Amazon Eastern Active Germplasm Bank (BAG Pataua palm). The fruits were evaluated for six characters and submitted to statistical analysis using four methods to estimate the coefficients of repeatability, determination and the number of fruits. The repeatability coefficients showed medium to high magnitudes. The same was true of the coefficients of determination, showing considerable accuracy for most of the characters with a sample of five fruits. For high accuracy in fruit evaluation (R2>90%) the desired sample for most characters would be 13 fruits, except for thickness (EP and EA). The methods showed a similar number of measurements for most of the characters in the three estimated percentages. Therefore, thirteen to 24 fruits are needed for a desirable sample of all the characters in the germplasm of this palm, with an accuracy of up to 95%.